The Relationship between Theory of Constraints and System Dynamics in Operations Management - Chaudhary, Satya Narayan (Journal of Development Review, 2021)
The main purpose of this article is to examine the relationship of theory of constraints with system dynamics in operations management. The paper also aims at the presentation of examples showing how deficient managerial decision-making in operations management can be. The theoretical and literature-based article ends with an investigation of the intersection of the theory of constraints and system dynamics. Supporting indications are gathered from different fields of science, for instance, decision science, psychology, sociology, and biology. Examples of apparently deficient decision-making in production contexts are given. It is shown how the theory of constraints and the broader field of system dynamics offers concepts and methods to mitigate some issues of poor decision-making. The complexity of decision making can be eased in the modern business world with the help of the relationship of theory of constraints with system dynamics.